(3eNJUQ GdbOhQjs - (3GdbOhQj, CHh GdMSjf, CMeO Hf eMeO Hf CMeO Hf LYaQ Hf MeOGf, J (B428(3g`s ((3bGSe Hf EHQGgje GdhJGQs)
(3ChdgG (B:s
(3HSe Gddg(B...(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf(B...(3CeG HYO bGd GdTjN GdEeGe(B...(3GdeYQha HGdbOhQj(B...(3cJGH GdWgGQIs
(3BNQgG (B:s
(3hBNQg ef (B((3MSGH GdaQGFV(B) (3bhdg(B: (3hEPG UMJ eSCdI GdefGSNI hCQOJ eYQaI eG jUjH cd hGMO ef MHGJ GdOQge bSeJ eG UMJ efg GdeSCdI Ydi KeGfjI hCQHYjf (B...(3hGddg CYde HGdUhGHs
(3aj BNQgG agQS, hgj fSNI eUMMI(B.s
(3JHUQI GdYfhGf (B:s
((3GdeNJUQ aj abg GdMfajI(B)s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B1(3,U(B212s
(3eYLe GdeDdajf(B:(3L(B1(3,U(B242s
Keywords: (3Gdabg GdMfajs